2017
DOI: 10.2169/internalmedicine.8500-16
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Chest X-ray Scores and the Clinical Findings in Children and Adults with <i>Mycoplasma pneumoniae</i> Pneumonia

Abstract: Objective To compare the radiological and laboratory data of children and adults with Mycoplasma pneumoniae pneumonia (MPP) and to evaluate the correlation between the total affected lung area and the clinical findings. Methods We retrospectively examined the data from MPP patients who visited our hospital during the period from April 2006 to July 2014. All data were retrieved at the time of the diagnosis of MPP and were analyzed to investigate the correlation between the clinical findings and the total affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
(10 reference statements)
3
12
0
Order By: Relevance
“…Regarding the radiological findings, we found that the interstitial pattern was the most frequent in both groups (78%; P =0.372), as has been reported in Poland (85.8%) 42. In Japan, the interstitial pattern was documented only in 28.2% of the patients, whereas the consolidation pattern was the most common radiological finding (87.3%), followed by bronchopneumonia (60.6%) 59. In this study, bronchopneumonia was observed in 29.3% of the patients and consolidation only in 7.3%, other studies have reported consolidation as the most common radiological finding 36,60.…”
Section: Discussionsupporting
confidence: 76%
“…Regarding the radiological findings, we found that the interstitial pattern was the most frequent in both groups (78%; P =0.372), as has been reported in Poland (85.8%) 42. In Japan, the interstitial pattern was documented only in 28.2% of the patients, whereas the consolidation pattern was the most common radiological finding (87.3%), followed by bronchopneumonia (60.6%) 59. In this study, bronchopneumonia was observed in 29.3% of the patients and consolidation only in 7.3%, other studies have reported consolidation as the most common radiological finding 36,60.…”
Section: Discussionsupporting
confidence: 76%
“…CXR taken in supine position 5.9 h (SD± 1.8) after the respective prone positioning were evaluated independently by two board-certified radiologists. To assess changes in pulmonary opacification after intubation and prone positioning, respectively, a CXR scoring system was applied as described previously [17] .…”
Section: Methodsmentioning
confidence: 99%
“…There has been some research on the predictors of refractory M. pneumoniae pneumonia. Large-scale pulmonary morphogenesis, extrapulmonary complications, and elevated CRP and LDH are clinically relevant risk factors for refractory M. pneumoniae pneumonia 10 – 12 . However, the current prediction methods often use only a single indicator to judge the prognosis, or there are few clinical data and no prospective verification.…”
Section: Introductionmentioning
confidence: 99%